Web usability survey measurement - Ayu, Media Anugerah; Zakaria, Noor Azura (IIUM Press, 2011)

(untitled)
Web development process which is ignoring the users' perspectives frequently meets failure and high risk when the end product is categorised as unusable and rejected by the targeted users. It is imperative the web development to incorporate the user-centred design process in ensuring to produce a usable and successful output which is acceptable by the users as well as clients. One of the techniques in assessing the web usability is by conducting survey that incorporates with relevant measurement that associated with user's requirements and needs.